Implication of explicit knowledge and subjective evaluation in procedural perceptual-motor learning - Sarah Seiwert; Elodie Martin; Elodie Martin; Elodie Martin; Yannick Lagarrigue; David Amarantini; Lilian Fautrelle; Joseph Tisseyre; Jessica Tallet (Frontiers in Behavioral Neuroscience)
IntroductionProcedural Perceptual-Motor Learning (PPML) enables the acquisition of new motor procedures and is fundamental for a wide range of human behaviors. While traditional research has focused on task-related characteristics, there is growing interest in individual factors to account for inter-individual differences in PPML. This study aims to investigate the roles of two individual factors related to learners’ strategies and mindsets: (a) explicit knowledge of the task’s characteristics and regularities and (b) subjective evaluation of the task and performance. We hypothesized that (a) participants reporting explicit knowledge of the task would exhibit higher PPML scores compared to those who did not, and (b) PPML scores would be related to subjective evaluation.MethodsParticipants were invited to practice two types of PPML tasks: motor sequence learning assessed by a Serial Reaction Time Task (SRTT) (Experiment 1) and visuomotor adaptation assessed by a Target Jumping Task (TJT) (Experiment 2). After each task, they were asked to answer post-learning questions about (a) their explicit knowledge of the task’s rules and (b) their subjective evaluations, including perceived levels of stress, tiredness, motivation, attention, and perceived progress.ResultsThe findings of Experiment 1 revealed that participants reporting explicit knowledge of the SRTT exhibited higher learning scores, which were related to perceived stress and progress. In Experiment 2, participants reporting explicit knowledge of the TJT exhibited lower learning scores, which were related to perceived stress, tiredness, concentration, and progress.DiscussionThis study offers a novel and comprehensive perspective on inter-individual differences in PPML by considering the roles of explicit knowledge and subjective evaluations in two types of PPML tasks. Although further replication and generalization are necessary, the findings provide valuable insights into how learner-task interactions may explain inter-individual differences and highlight the importance of considering participants’ subjective reports research for future studies on PPML.